NILAI NASIONALISME YANG TERKANDUNG DALAM KAMI, PEREMPUAN KARYA ARMIJN PANE: KAJIAN PASCAKOLONIAL - Christopher Allen Woodrich (Universitas Sanata Dharma, 2013)
The Japanese invasion of the Dutch East Indies in 1942 did nothing to kill the blossoming nationalism which had swept throughout the colony in since the early 20th century. Although the Japanese viewed Indonesia as a source of resources to fuel their war efforts, training Indonesians to protect this vision, the Indonesians themselves used the situation to modernise their military techniques in preparation for a revolution. Such efforts are evident in Kami, Perempuan, a short stage play from 1943 written by Armijn Pane. In showing the interactions between the spaces of the individual and the nation, he ignores the implications of the new military units intended purpose and, as such, renders it unimportant. He also expresses concern that the individualistic and self-serving ideals promoted by the Dutch colonials would hinder the cause for freedom.Key words : Armijn Pane, Kami Perempuan, Nationalism, PETA.